COMPARISON OF THE EFFECTIVENESS AND SAFETY OF FLEXIBLE ENDOSCOPIC NEPHROLITHOTOMY AND PERCUTANEOUS MICROTUNNEL NEPHROLITHOTOMY IN THE TREATMENT OF 10–30 MM KIDNEY STONES AT XANH PÔN GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To compare the effectiveness and safety of flexible ureteroscopic lithotripsy (retrograde intrarenal surgery – RIRS) and super-mini percutaneous nephrolithotomy (SMP) in the treatment of renal stones measuring 10–30 mm at Saint Paul General Hospital.Methods: A retrospective comparative study was conducted. The RIRS group included 62 patients treated. The SMP group included 120 patients treated by 14F super-mini percutaneous nephrolithotomy without ureteral catheter placement and with ultrasound-guided renal access. Operative time, stone-free rate, postoperative complications according to the Clavien–Dindo classification, and length of hospital stay were analyzed.Results: The mean stone size was 20.8 ± 7.8 mm in the RIRS group and 24.7 ± 8.3 mm in the SMP group. The operative time was longer in the RIRS group (60.8 ± 8.6 minutes) than in the SMP group (32.8 ± 23.2 minutes). The early stone-free rate was 83.9% for RIRS and 95.0% for SMP; the one-month stone-free rate of SMP reached 97.7% without additional interventions. Complications were mostly mild in both groups, and no major complications or mortality were recorded. The mean hospital stay was shorter in the SMP group.Conclusion: Both RIRS and SMP are safe and effective options for renal stones measuring 10–30 mm. RIRS is suitable for selected patients with smaller stones or higher bleeding risk, whereas SMP provides higher stone-free rates, particularly for stones ≥20 mm and lower-pole stones. These techniques should be considered complementary rather than competitive.
Keywords: Renal stones; flexible ureteroscopy; retrograde intrarenal surgery; super-mini percutaneous nephrolithotomy